Trafficking, Client and Police Violence, Sexual Risk and Mental Health Among Women in the Sex Industry at the Thai-Myanmar Border - Decker, Michele R. (Violence against women, 2022)
This study describes sex trafficking and associations with violence and health among female migrants in the sex industry in Mae Sot, Thailand. The mixed-methods study included a qualitative interview phase (n = 10), followed by a cross-sectional survey phase (n = 128). Entry via trafficking (force, fraud, or coercion [FFC], or as minors) was prevalent (76.6%), primarily FFC (73.4%). FFC was associated with inconsistent condom use, inability to refuse clients, poor health, and anxiety. Past-year violence was normative including client sexual violence (66.4%), client coercion for condom nonuse (> 95%), and police extortion (56%). Working conditions enabled violence irrespective of mode of entry. Profound unmet needs exist for safety and access to justice irrespective of trafficking history.